Construction safety and performance in Malaysian construction industry: a review - Albarkani, Mosab Sultan Saeed; Shafii, Haryati (UTHM Publisher, 2021)
Major construction projects in Malaysia are subjected to unsafe conditions that can result in accidents and subsequently undermine the project’s safety results. Despite alarming, studies examining the factors that influence the performance of the Malaysian construction industry remain scarce. Hence, this paper aims to review the literature related to construction safety performance in the Malaysian construction industry. In particular, this paper gives emphasis in reviewing the literature on construction safety and performance, safety performance in the construction industry, construction safety performances, security management, safety programme, safety policy, cost of safety, and safety training. The findings of the analysis revealed that proper construction safety activities would lead to the overall performance of the Malaysian construction industry.